New measurements of crustal and lithospheric thickness for the South American platform using the receiver function method, toward a 3D velocity model - Vera, Julia Carolina Rivadeneyra (2021)
Using the Permanent Brazilian Network and a temporary deployment, we studied the Moho discontinuity and the Lithosphere-Asthenosphere Boundary (LAB) in the stable South American platform. From P-wave receiver functions processed with a modified, low uncertainty, H-k stacking method, we obtained the Moho depth; that together with previous results permitted to updated the crustal thickness map of South America, with improved resolution in the Amazon and western part of Brazil, and better delimiting the narrow belt of thinner Sub-Andean crust. The average crustal thickness in the stable continental region is 40.5 km. Paraná and Parnaba intracratonic Basins, the western part of Pantanal Basin and Amazon Craton present a thicker crust up to 44 km. The eastern edge of Pantanal Basin, Borborema, and Mantiqueira Provinces present a thinner crust, up to 36 km. Vp/Vs ratios were estimated for the first time on a large scale in the South American platform. Values ranged between 1.68 and 1.80, being higher in the Paraná Basin and coastal margin (up to 1.79) and lower in cratonic areas (< 1.74). Nevertheless, regional patterns are hard to establish due to the scattered estimations. The LAB was estimated using the S-wave receiver function method, also analyzing some local international stations. At the Borborema and Mantiqueira Provinces, we confirm a thinner lithosphere of 90 km that also characterizes the Chaco and Pantanal Basins. The Amazon Craton, the São Francisco Craton, and Paranapanema block present a thicker, greater than 120 km lithosphere; in these older and colder areas, we also interpreted a mid-lithospheric discontinuity at 90 km, which tends to correlate with the heat flow. Nevertheless, we do not observe a clear correlation between the heat flow and deeper LAB measurements. On the other hand, the seismicity follows areas with thinner observed lithosphere. Finally, due to the need of using 3D velocity models for regional accurate epicenter locations, that improves neotectonic and seismic hazard studies, we have built a 3D a-priori velocity model for the South American Platform including the Central Andes area. The model is based on previous velocity relationships and structural information, being the most important the obtained crustal thickness. The horizontal resolution is 0.5º, and the vertical varies from 1 km at shallower depths to 5 km in the upper mantle. The travel time difference between the 3D and 1D velocity models is larger than 8 seconds for a station on the stable platform predicting an Andean event travel time. To test the model reliability, we relocated the well-known Aiquile 1998 earthquake (Bolivia) and recent platform events, obtaining successful results when compared with the best epicenters.